2021
DOI: 10.1039/d1ra04835j
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-based drug delivery systems as promising carriers for patients with COVID-19

Abstract: We propose a consideration of Avigan-loaded nano-emulsions as a promising nano-based delivery system for the treatment of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 179 publications
(237 reference statements)
0
19
0
Order By: Relevance
“…Therefore, liposomes, nanoemulsions, and patches based on the micro needle are being investigated in preclinical studies, which may be proven as viable alternatives to invasive techniques [119]. The lipidic nanoparticles have proven exceptional applications in delivering the mRNA vaccine for COVID-19 infection, as evident from Moderna and BioNTech/Pfizer [124]. Moreover, a novel silica nanoparticle, Nuvec ® , has the potential to be administered as a viral vector or as a delivery system for the transfer of genetic material into host cells [125].…”
Section: Drug Delivery Route and Delivery Systemsmentioning
confidence: 99%
“…Therefore, liposomes, nanoemulsions, and patches based on the micro needle are being investigated in preclinical studies, which may be proven as viable alternatives to invasive techniques [119]. The lipidic nanoparticles have proven exceptional applications in delivering the mRNA vaccine for COVID-19 infection, as evident from Moderna and BioNTech/Pfizer [124]. Moreover, a novel silica nanoparticle, Nuvec ® , has the potential to be administered as a viral vector or as a delivery system for the transfer of genetic material into host cells [125].…”
Section: Drug Delivery Route and Delivery Systemsmentioning
confidence: 99%
“…Non-pharmacological countermeasures should be considered as an important approach as many countries do not have adequate sources of medicines and vaccines to prevent SARS-CoV-2 infection. Since the most important way of transmission is through aerosol droplets, it is necessary to use a facemask in public places, take care of contaminated hands and follow the usual hygienic methods [ 34 ]. Pathogens such as SARS-CoV-2 can remain on inanimate surfaces for more than 9 days [ 35 ].…”
Section: Preventionmentioning
confidence: 99%
“… The most common nanomaterials in drug delivery applications and their preparation methods. Reproduced with permission from [ 34 ]. Copyright American Chemical Society,2020.…”
Section: Figurementioning
confidence: 99%
“…However, FPV is a hydrophobic molecule with low solubility in water (8.7 mg/mL) as well as a short half-life, leading to rapid renal clearance in its hydroxylated form [31]. Therefore, the use of a nanocarrier such as lipid-based nano-formulations, nano-emulsion, and polymeric nanoparticles (NPs) is a rational approach to overcome the abovementioned limitations of FPV [32][33][34]. In addition, the use of biodegradable polymers as nanocarriers has been recognized by the FDA to enhance the drugs' stability and solubility [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Chun et al demonstrated that the co-encapsulation of FPV and mir-323a into amphiphilic copolymersomes enhanced in vitro cellular uptake and consequently resulted in a synergistic effect in controlling H1NI virus infection [34]. In another study, FPV-loaded nano-emulsion was postulated to facilitate the binding to the virus RNA-dependent RNA polymerase, prevent the SARS-CoV-2 virus replication, and destroy the viral structure [33]. In addition, liposomes, polymeric NPs and micelles have been used in pulmonary inhalation routes to improve medication efficacy and target drug delivery [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%